Perancangan Interior Coffee Shop dengan Fasilitas Belajar untuk Mahasiswa di Denpasar - Clara Leonita; Lintu Tulistyantoro (Intra, 2018)
The development of the era is occurring along with the change in people’s lifestyle, particularly in the life of students. Their time are often consumed by studying, leaving very little room for entertainment. This phenomenon has triggered entrepreneurs to view the coffee shop as a promising business opportunity. Many coffee shops today offer a one-stop shopping system such that visitors can fulfill their various desires altogether at a single place. This research develops the idea of a Collaborative Coffee Shop as a place that can accommodate the multiple needs of students as well as the general public, such as working, interacting, collaborating, having discussions and doing other activities that can enrich the ideas of each individual. The objective of this research design project is to create an interior design with the Collaborative concept that can improve productivity, creativity and business development of the Collaborative Coffee Shop users. The method used in this design process is the Design Thinking method, consisting of six steps, which are (1) Empathize and Define, (2) Research, (3) Ideate, (4) Prototype, (5) Test, and (6) Implement. Additional facilities designed in this research include an educative playground, a personal area, a modular workstation, and a play area to support the Collaborative concept. The benefits that students, particularly in Surabaya, can take privilege of with the existence of this coffee shop is a modular facility and an open space system that can provide a more relaxed working atmosphere and encourage social interaction among individuals